2005
DOI: 10.1161/01.hyp.0000160404.08866.5a
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Treatment Prevents Renal Damage and Dysfunction and Reduces Arterial Pressure in Salt-Sensitive Hypertension

Abstract: Abstract-The goal of this study was to test the hypothesis that oxidative stress in Dahl salt-sensitive (SS) rats on a high-sodium intake contributes to the progression of renal damage, the decreases in renal hemodynamics, and the development of hypertension. We specifically studied whether antioxidant therapy, using vitamins C and E, could help prevent renal damage and glomerular filtration rate (GFR) and renal plasma flow reductions and attenuate the increases in arterial pressure. Thirty-three 7-to 8-week o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 26 publications
12
110
0
Order By: Relevance
“…Increased vitamin C concentration in the fi ltrate may competitively inhibit uric acid reabsorption (30). Both human and animal studies have demonstrated that administration of vitamin C increases renal plasma fl ow and glomerular fi ltration rate (31,32) to lower serum uric acid concentration. Vitamin C could reduce oxidative stress and infl ammation to lower uric acid synthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Increased vitamin C concentration in the fi ltrate may competitively inhibit uric acid reabsorption (30). Both human and animal studies have demonstrated that administration of vitamin C increases renal plasma fl ow and glomerular fi ltration rate (31,32) to lower serum uric acid concentration. Vitamin C could reduce oxidative stress and infl ammation to lower uric acid synthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that rats receiving a high sodium diet that caused increased arteriolar and venular O 2 Ϫ1 production exhibited severe renal damage, decreased GFR and renal plasma flow, and high renal superoxide production (29 -30 ). Furthermore, treatment with vitamin C and E decreased the production of renal superoxide and renal damage, and prevented the decrease in renal hemodynamics (31 ). Recent human studies indicated that individuals with essential hypertension have decreased antioxidant capacity and produce excessive amounts of ROS, and that more than half of these hypertensive patients were salt sensitive and had progressive renal damage (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 It is likely that a higher responsiveness of the P2X 7 pathway in the DS rats may aggravate inflammation in the kidney that has been damaged by hypertension. High-salt-containing diets in DS rats induced increased blood pressure, urinary protein excretion, renal interstitial fibrosis, macrophage infiltration and T-cell infiltration.…”
Section: P2x 7 Expression Is Higher In the Kidneys Of Ds Ratsmentioning
confidence: 99%